Neural Stem Cell-Derived Extracellular Vesicles Counteract Insulin Resistance-Induced Senescence of Neurogenic Niche. Issue 3 (21st January 2022) - Natale, Francesca; Leone, Lucia; Rinaudo, Marco; Sollazzo, Raimondo; Barbati, Saviana Antonella; La Greca, Francesco; Spinelli, Matteo; Fusco, Salvatore; Grassi, Claudio
Abstract: Neural stem and progenitor cell (NSPC) depletion may play a crucial role in the cognitive impairment observed in many age-related non-communicable diseases. Insulin resistance affects brain functions through a plethora of mechanisms that remain poorly understood. In an experimental model of insulin resistant NSPCs, we identified a novel molecular circuit relying on insulin receptor substrate-1 (IRS-1)/ Forkhead box O (FoxO) signaling cascade and inhibiting the recruitment of transcription factors FoxO1 and FoxO3a on the promoters of genes regulating proliferation and self-renewal. Insulin resistance also epigenetically increased the expression of cyclin-dependent kinase inhibitor 1 (p21) and accelerated NSPC senescence. Of note, we found that stimulation of NSPCs with NSPC-derived exosomes (exo-NSPC) rescued IRS-1/FoxO activation and counteracted both the reduced proliferation and senescence of stem cells. Accordingly, intranasal administration of exo-NSPC counteracted the high-fat diet-dependent impairment of adult hippocampal neurogenesis in mice by restoring the balance between proliferating and senescent NSPCs in the hippocampus. Our findings suggest a novel mechanism underlying the metabolic control of NSPC fate potentially involved in the detrimental effects of metabolic disorders on brain plasticity. In addition, our data highlight the role of extracellular vesicle-mediated signals in the regulation of cell fate within the adult neurogenic niche. Graphical Abstract: Intranasal administration of neural stem cell-derived exosomes counteract the high-fat diet-dependent depletion of hippocampal neurogenic niche.